Fragrance Formation in Aquilaria spp. Shoot Culture Induced by Acremonium sp. - GAYUH RAHAYU (Indonesian Society for microbiology, 2010)
In this research, fragrance formation in the shoot culture of three clones of Aquilaria malaccensis (Ama1, Ama7, and Ama13) and four clones of A. microcarpa (Ami5, Ami8, Ami16, and P6) as a response towards infection of four isolates of Acremonium sp. (F, G, L, and M) were studied using dual culture methods in three different concentrations of a modified Murashige-Skoog (MSmod) media (50, 75, and 100%). The result indicated that Acremonium F and M induced the formation of fragrance. The index of fragrance induced by Acremonium F was twice from that of Acremonium M, and commonly produced in shoot cultures in MSmod 50%. The index of fragrance in A. malaccensis shoot culture was 70% higher than that of A. microcarpa. Furthermore, GLC analyses of acetone extracted from fragranced shoots of A. malaccensis indicated that only one compound (RT 5.76) might determine the fragrance. Host-microbe compatibility study indicated that the presence of Acremonium significantly affected the fitness of the shoots. In contrast, the presence of shoots did not significantly affect the growth rate of Acremonium. In general, Acremonium F, L and M significantly increased shoot death during the 35 days of interaction.